Impact of Arterial Calcification on Cardiovascular and Renal Outcomes in Kidney Transplant Patients - Joohyung Ha; Jong Cheol Jeong; Jung-Hwa Ryu; Myung-Gyu Kim; Kyu Ha Huh; Kyo Won Lee; Hee-Yeon Jung; Kyung Pyo Kang; Han Ro; Seungyeup Han; Beom Seok Kim; Jaeseok Yang (Karger Publishers, 2024)
Introduction: Coronary artery calcification score (CACS) and abdominal aortic calcification score (AACS) are both well-established markers of vascular stiffness, and previous studies have shown that a higher CACS is a risk factor for chronic kidney disease (CKD) progression. However, the impact of pretransplant CACS and AACS on cardiovascular and renal outcomes in kidney transplant patients has not been established. Methods: We included 944 kidney transplant recipients from the KoreaN cohort study for Outcome in patients With Kidney Transplantation (KNOW-KT) cohort and categorized them into three groups (low, medium, and high) according to baseline CACS (0, 0 < and ≤100, >100) and AACS (0, 1-4, >4). The low (0), medium (0 < and ≤ 100), and high (>100) CACS groups each consisted of 462, 213, and 225 patients, respectively. Similarly, the low (0), medium (1-4), and high (>4) AACS groups included 638, 159, and 147 patients, respectively. The primary outcome was the occurrence of cardiovascular events. The secondary outcomes were all-cause mortality and composite kidney outcomes, which comprised of >50% decline in the estimated glomerular filtration rate and graft loss. Cox regression analysis was used to investigate the association between baseline CACS/AACS and outcomes. Results: The high CACS group (N = 462) faced a significantly higher risk for cardiovascular outcomes (adjusted hazard ratio [aHR], 5.97; 95% confidence interval [CI], 2.01-17.7) and all-cause mortality (aHR, 2.74; 95% CI, 1.27-5.92) compared to the low CACS group (N = 225). Similarly, the high AACS group (N = 638) had an elevated risk for cardiovascular outcomes (aHR, 2.38; 95% CI, 1.16-4.88). Furthermore, the addition of CACS to prediction models improved prediction indices for cardiovascular outcomes. However, the risk of renal outcomes did not differ among CACS or AACS groups. Conclusion: Pretransplant arterial calcification, characterized by high CACS or AACS, is an independent risk factor for cardiovascular outcomes and mortality in kidney transplant patients.